TB epidemiology: where are the young women? Know your tuberculosis epidemic, know your response - Rubeshan Perumal; Kogieleum Naidoo; Nesri Padayatchi (BMC, 2018)
Abstract Background The global predominance of tuberculosis in men has received significant attention. However, epidemiological studies now demonstrate that there is an increased representation of young women with tuberculosis, especially in high HIV burden settings where young women bear a disproportionate burden of HIV. The role of the HIV epidemic, as well as changes in behavioural, biological, and structural risk factors are explored as potential explanations for the increasing burden of tuberculosis in young women. Discussion As young women are particularly vulnerable to HIV infection in sub-Saharan Africa, it is unsurprising that the TB epidemic in this setting has become increasingly feminised. This age-sex trend of TB in South Africa is similar to WHO estimates for other countries with a high HIV prevalence where there are more female than male cases notified up to the age of 25 years. The high prevalence of anaemia of chronic disease in young women with HIV is an additional potential reason for their increased TB risk. The widespread use of injectable medroxyprogesterone acetate contraception, which has been shown to possess selective glucocorticoid effect and oestrogen suppression, in young women may be an important emerging biological risk factor for tuberculosis in young women. Behavioural factors such as alcohol use and tobacco smoking patterns are further factors which may be responsible for the narrowing of the sex gap in TB epidemiology. In comparison to the significantly higher alcohol consumption rates in men globally, there is a narrowing gap in alcohol consumption between the sexes in South Africa with alarming rates of alcohol abuse in young women. There is a similar narrowing of the tobacco smoking gap between the sexes in South Africa, with increasing smoking prevalence in young women. Conclusion With nearly 70% of all TB patients being co-infected with HIV in our setting, it is not surprising that the age and sex distribution of TB is increasingly resembling the distribution of HIV in this region of dual hyperendemicity. New TB service design must begin to reflect the presence of young women as a significant group burdened by the disease.